Penguatan Pendidikan Karakter melalui Pembelajaran Sejarah Berbasis Kitab Kuntara Raja Niti - Andika Dian Ifti Utami; Warto Warto; Sariyatun Sariyatun (Universitas Negeri Malang, 2018)
This study aims to strengthen the character of the students so that they have a national identity. Strengthening of character in society can be built through the utilization of local history which have moral values. Historical sources such as Kitab Kuntara Raja Niti contains values that are believed to create an attitude of peace, friendship, responsibility, tolerance, the spirit of nationalism, care for the environment, social care, religious, recognize excellence, independence and discipline. The importance of this study is based on the assumption that cultural heritage is an educational component that can foster a sense of belonging and respect their own cultural history. Kitab Kuntara Raja Niti consist of ideas and guidance of mankind's relationship with God, the community and the natural environment that can be a filter to face of global cultural transformation and playa role in strengthening national identity. So that these values are very relevant to be taken in history as character education for students. This study uses a qualitative method, by collecting documents related to the Kitab Kuntara Raja Niti either Indigenous Book, Journal, Manuscripts-Manuscripts or other documents relating to the object, and then analyzed through descriptive approach.DOI: http://dx.doi.org/10.17977/um033v1i12018063